Role of temperature and particle size on wood-waste composite 3D printing - Toh, Ming Xian (Nanyang Technological University, 2024)
Wood waste is widely available worldwide as a by-product of the lumber industry and landscaping. There is a potential solution to extend its life cycle by incorporating it into biodegradable Polylactic Acid (PLA) polymer to create high-value products with the use of three-dimensional (3D) printing. The introduction of 3D printing technologies into the industry has enabled things to be produced quickly and at a relatively affordable price as compared to traditional manufacturing methods. 3D printing creativity and flexibility in producing complex designs without the equipment restrictions associated with traditional manufacturing methods. This technology allows for the creation of intricate shapes and structures that might be challenging or impossible to achieve using traditional manufacturing. This paper discusses different manufacturing methods including different 3D printing processes. The impact of printing temperature and particle sizes on mechanical and aesthetic properties was investigated in this paper and aims to develop a composite suitable for small- and large-scale printing. The findings in this paper allow for a deeper understanding of the influence of wood particle size on composite mechanical and thermal properties, while also shedding light on the visual effects of printing temperature variations.